2015
DOI: 10.11648/j.ajtab.20150103.11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Selected Macroeconomic Variables on Stock Market in India

Abstract: Purpose of the study: The present study investigates the influence of selected macroeconomic variables in terms of international crude oil price, exchange rates, domestic gold price, real interest rates and wholesale price index on stock market indices (sensex and nifty) of India. Background: Macroeconomic variables directly or indirectly affect the stock prices because it influences strongly the stock returns by affecting the stock prices, which supports the existance of a long-run relationship between the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, there is no relative importance between the price of gold and oil. In addition, macroeconomic factors implementing the relevant policies and results show there has been an adverse impact on the Malaysian Stock Exchange as well as in further research (Bhunia and Ganguly, 2015;Singh, 2014a).…”
Section: The Basic Aim Of the Researchmentioning
confidence: 93%
See 1 more Smart Citation
“…However, there is no relative importance between the price of gold and oil. In addition, macroeconomic factors implementing the relevant policies and results show there has been an adverse impact on the Malaysian Stock Exchange as well as in further research (Bhunia and Ganguly, 2015;Singh, 2014a).…”
Section: The Basic Aim Of the Researchmentioning
confidence: 93%
“…This research utilized the FAVAR model to measure all macroeconomic factors that influence gold prices and trends (Long and Hanh, 2019). Bhunia and Ganguly (2015) examined the effects of IR, commodity prices and the conversation rate on stock market performance in Malaysia and showed the relationship among variables included exchange rates and bonds. The results concluded that the IR and exchange rate indicate positive and significant relationships between them.…”
Section: The Basic Aim Of the Researchmentioning
confidence: 99%